Osteoclast Deficiency Contributes to Temporomandibular Joint Ankylosed Bone Mass Formation. (October 2015) - He, L.H.; Xiao, E.; Duan, D.H.; Gan, Y.H.; Zhang, Y.
Ankylosed bone mass in temporomandibular joint ankylosis (TMJA) is an important factor affecting mouth-opening limitation. However, the mechanism underlying the occurrence of ankylosed bone mass remains unknown. Research has shown that osteoblasts and osteoclasts maintain balance in bone remodeling. Thus, we hypothesized that aberrant osteoclastogenesis and osteogenesis may be involved in the occurrence of ankylosed bone mass in TMJA. In this study, we characterized the osteogenesis of bone marrow stem cells and the osteoclastogenesis of myelomonocyte in clinical specimens of TMJA and normal controls. Results showed that, compared with control bone marrow stem cells, TMJA bone marrow stem cells had lower proliferative and osteogenic capacities. The number of osteoclasts in the ankylosed bone mass group dramatically decreased, and myelomonocyte osteoclastogenic potential was impaired. The RANKL/OPG ratio of the ankylosed bone mass group was lower than that of the control group. Thus, our study suggests that osteoclast deficiency may be an important factor affecting bone mass ankylosis.